Interpretation of the Concept of “Enterprise” in the Context of Latin American Legal Scholars’ Contemporary Ideas on the Tasks of Civil and Commercial Codifications - Michailovna Belikova, Ksenia (International Journal of Criminology and Sociology, 2022)
The relevance of the study is connected with its complex nature, giving an understanding of the vector of development of civil and commercial codifications in some Latin American countries, based on recent statutory regulations, which were not previously adequately reflected in the doctrine. From this perspective, therefore, this study fills the gap in the relevant knowledge. The author examines the features of the legal regime in certain Latin American countries to comprehend and show which trends prevail in a particular country and how this is reflected in the tasks of civil and commercial codifications. Thereby, the results obtained by the author are given in a comparative aspect in the context of Latin American legal experts’ ideas on the tasks of civil and commercial codifications concerning the legal recognition of the interpretation of the concept of “enterprise”.